2020
DOI: 10.3389/fmicb.2020.544653
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Virulence, Antimicrobial Resistance, and Molecular Characterization of Pseudomonas aeruginosa Isolates From Drinking Water in China

Abstract: Pseudomonas aeruginosa is an important opportunistic pathogen and remains a major threat to the microbial safety of drinking water. There is a lack of comprehensive data on P. aeruginosa contamination in drinking water in China. Therefore, this study aimed to determine the prevalence, genetic diversity, virulence genes, and antimicrobial resistance of P. aeruginosa isolated from mineral water and spring water in China. From January 2013 to January 2014, 314 drinking water samples were collected from 23 cities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…Szita et al [ 2 ] reported 94 contaminated samples with P. aeruginosa out of 160 well water samples [ 2 ]. Wei et al [ 13 ] reported 77 cases (24.5%) of P. aeruginosa from mineral water and spring water samples collected in China [ 14 ]. According to previous research by Wu et al [ 16 ], P. aeruginosa contamination in raw water (30.4%) and activated carbon filtered water (38.6%) was significantly higher than in raw water (3.9%) [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Szita et al [ 2 ] reported 94 contaminated samples with P. aeruginosa out of 160 well water samples [ 2 ]. Wei et al [ 13 ] reported 77 cases (24.5%) of P. aeruginosa from mineral water and spring water samples collected in China [ 14 ]. According to previous research by Wu et al [ 16 ], P. aeruginosa contamination in raw water (30.4%) and activated carbon filtered water (38.6%) was significantly higher than in raw water (3.9%) [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Wei et al [ 13 ] reported 77 cases (24.5%) of P. aeruginosa from mineral water and spring water samples collected in China [ 14 ]. According to previous research by Wu et al [ 16 ], P. aeruginosa contamination in raw water (30.4%) and activated carbon filtered water (38.6%) was significantly higher than in raw water (3.9%) [ 13 ]. Stoler et al [ 17 ] reported that 41% of 80 water samples were positive for P. aeruginosa .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an opportunistic pathogen that can be fatal for immunocompromised patients in whom it can cause infections of the blood, lungs, urinary tract, eye, ear or other parts of the body after surgery. It is also recognized as a major cause of resistant infections due to its ability to form biofilms (Wei et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…LasB , an important extracellular virulence factor that belongs to the protease category of enzymes, plays a crucial role in the pathogenicity of P. aeruginosa during infection ( Thibodeaux et al, 2007 ). Moreover, lasB was the most frequent virulence gene identified in screens for virulence factors in patients of Northwestern Morocco (98.7%), children with cystic fibrosis in Iran (95.4%), patients with community- and hospital-acquired diarrhea (98%), and mineral water and spring water in China (100%) ( Faraji et al, 2016 ; Elmouaden et al, 2019 ; Fakhkhari et al, 2020 ; Wei et al, 2020 ). Considering the wide distribution of lasB , this virulence gene was selected as the target for the assay developed in the current study.…”
Section: Discussionmentioning
confidence: 99%